Data depth and core-based trend detection on blockchain transaction networks - Zhu, Jason; Khan, Arijit; Akcora, Cuneyt Gurcan (Frontiers in Blockchain, 2024)
Dear Editor and reviewers of the Frontiers in Blockchain journal, We thank the two reviewers and the editor for their excellent comments and useful suggestions that helped improving our work, in particular, its presentation, background, and additional experiments. In the following, we summarize the main changes in this revised version.• We extended our empirical assessment by reporting NF-IAF score percentiles for the additional days of May 7 and May 9, 2022 in Table 4 and added a paragraph summarizing our results in Section 6.3.1: Experiment 1: The Collapse of LunaTerra.We thank you for the detailed review. Below are our responses to your comments and the changes made in response to the specific comments.Comment 1 (Misleading Title): The paper title seems misleading, as the main focus is not on e-crimes. Instead, the paper focuses more on trend analysis and the macro behavior of core users in the blockchain that affect the price. The authors briefly mentioned the LunaTerra case as an e-crime (lines 482-487). However, this is insufficient to motivate this classification as an e-crime case where the criminal benefits from fooling users.Response: Thanks for your suggestion. We agree and updated the title as: Data Depth and Core-based Trend Detection on Blockchain Networks.